Evaluation of drugs for the treatment of mastitis in regions without diagnostic laboratories. - Langenegger, Jerome; Coelho, Nilton Martins; Marques, Lúcia Maria Queiroz (Pesquisa Agropecuaria Brasileira, 2014)
For the economic treatment of bovine mastitis in regions without diagnostic laboratories, efficient drugs of large therapeutic spectrum, administered only once, are necessary. The efficacy of 12 drugs commercially used in Brazil were evaluated by only one treatment for each infected quarter. The drugs were tested against Streptococcus spp and Staphylococcus aureus in cows with subclinical mastitis. A large variation in the efficacy of the drugs was observed. Two of the drugs were equally efficient against the two groups of etiological agents, curing more than 75% of the infected quarters, and were considered to satisfy the minimal requirements. Four other drugs cured from 30 to 75% of the cases and were considered insufficient, but their efficacy could be improved with adequate reformulation. The six last drugs with less than 50% of cures were found inadequate for the used in the above described conditions.